Digital leadership, technological infrastructure, and digital readiness as determinants of employee performance in the telecommunications industry - Andi M Budihard; Titien Rahayuningsih; Asraf Asraf (Trigin Publisher, 2026)
Digital transformation has intensified the need for high-performing employees in the telecommunications industry. This study examines the effects of digital leadership, technological infrastructure, and digital readiness on employee performance. A quantitative explanatory design was employed using survey data from 182 employees in the telecommunications sector. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that digital leadership, technological infrastructure, and digital readiness have positive and significant effects on employee performance. Among these predictors, digital readiness has the strongest effect, indicating that employees’ ability, confidence, and adaptability in using digital technologies are critical for improving performance in digitally intensive work environments. The study contributes to digital transformation and employee performance literature by offering a socio-technical explanation of how leadership capability, technological support, and individual digital readiness jointly shape employee performance. Practically, the findings suggest that telecommunications companies should not only invest in technological infrastructure but also strengthen digital leadership and continuously develop employees’ digital readiness through training, coaching, and adaptive digital work systems.